PKM KELOMPOK TANI PADI DAN KELOMPOK TANI HORTIKULTURA DI DESA PUNGGUR KECIL KECAMATAN SUNGAI KAKAP KABUPATEN KUBU RAYA - Yulisa Fitrianingsih (Jurnal Buletin Al-Ribaath, 2018)
ABSTRACTFarmer groups in Punggur Kecil Village do not have rice milling machine, which causing high cost production. In addition, agricultural activities resulted unprocessed agricultural waste and causing acidic soils. On the other hand, agricultural waste has great potential for biomass as an alternative source of energy and soil conditioner. An alternative solution is provided to help farmers for processing agricultural waste, namely SUMBER, and for rice milling rice milling or rice huller. The objectives of this program are: a) To create independent farmer groups in the production processes of agricultural products. b) To processing agricultural waste into biomass c) To trigger community to actively involved in finding solution regarding agricultural waste problem which could reduce pollution from agricultural waste. d) applying biomass from agricultural waste as a soil conditioner that can increase the pH of agricultural soils. Keywords: Agricultural waste, biomass, horticulture, rice